Evaluación y caracterización de compuestos bioactivos en sacha manzano (Hesperomeles escalloniifolia Schltdl.) y upatankar (Berberis boliviana L). - Barragán Condori y Cols., Melquiades (2018)
Bioactive compounds were evaluated and characterized in two native fruits called sacha manzano (Hesperomeles escalloniifolia S) and upatankar (Berberis boliviana L), for which the anthocyanin pigments were extracted with acidified to 0.01% methanol, filtered and concentrated in a rotary evaporator. centrifuged, decanted and adjusted to a known volume for further analysis, purification and evaluation. In the extract the total anthocyanin content (CAT) was evaluated by the differential pH method, total polyphenols (PFT) by the Folin Ciocalteu method. The extract was then purified with set pak cartridge C-18 and in this solution the anthocyanin spectra were identified by FTIR and Visible UV. The extracts characterized by UV-Vis spectrophotometry have maximum absorbance values ​​at 520 nm corresponding to established anthocyanin structures, and FTIR-ATR spectroscopy shows strong absorption signals at different vibration frequency values ​​(cm-1) which correspond to functional groups of anthocyanins. The CAT values ​​are 978.83 and 75.39 (mg of cyanidin 3-glucoside / 100 g of fresh weight) of PFT 4902.41 and 1029.59 (mg of gallic acid / 100 g of fresh weight) for upatankar and sacha manzano tree respectively. The UV Vis and FTIR spectra correspond to anthocyanins. The high content of CAT and PFT of upatankar allows us to recommend its use as an antioxidant in functional foods and natural extracts in the agroindustry.